How to promote the social–emotional competence of rural left-behind children? An empirical study based on propensity score matching - Mo, Xiaolan; Shi, Gaojun; Zhang, Yanan; Xu, Xiao; Ji, Chengjun (Frontiers in Psychology, 2023)
Social-emotional competence (SEC) played an important role in promoting physical and mental development of children, but there existed huge gaps in SEC development between rural left-behind children. This study used propensity score matching (PSM) to investigated 578 rural children about the effects of being left-behind as well as individual characteristics and teacher support on their development of SEC. The results showed that being left-behind had significant negative effects on SEC of rural children; The development of SEC is various among the left-behind children of different gender and length of left-behind duration. Teacher support had a significant moderating effect on the influence path of SEC, which could effectively mitigate the negative effects of left-behind children. Therefore, this study played an implicative role for studying the development of left-behind children's SEC. The government and society should provide adequate cultural capital through completing the support system for compensating the lack of cultural capital. Schools and teachers should pay more attention to the development of left-behind children’s SEC through curriculum development and performance evaluation to create a positive atmosphere. Parents should promote SEC development for left-behind children by improving their personal communication and family parenting styles.